The influence of innovation on Corporate Sustainability in the International Banking Industry - Aracil Fernández, Elisa María; Forcadell, Francisco Javier; Úbeda, Fernando (My University)
We empirically explore the innovation and corporate sustainability link using a large sample of worldwide banks for the period 2003 2016. Our results suggest that service innovation performance enhances the banking industry s corporate sustainability. In addition, we contribute by proposing a conceptual framework for understanding the link between innovation performance and corporate sustainability in the banking industry. The framework consists of three underlying dimensions the antecedents of innovation performance, the specific innovation performance initiatives, and how these initiatives are converted into improved corporate sustainability. Our findings provide insights for academics and practitioners on the dynamics between service innovation performance and corporate sustainability in the banking sector. Further, due to the intermediation role of banks in the economy, their evolution towards sustainable banking constitutes a lever for sustainability across other industries and overall sustainable development

We empirically explore the innovation and corporate sustainability link using a large sample of worldwide banks for the period 2003 2016. Our results suggest that service innovation performance enhances the banking industry s corporate sustainability. In addition, we contribute by proposing a conceptual framework for understanding the link between innovation performance and corporate sustainability in the banking industry. The framework consists of three underlying dimensions the antecedents of innovation performance, the specific innovation performance initiatives, and how these initiatives are converted into improved corporate sustainability. Our findings provide insights for academics and practitioners on the dynamics between service innovation performance and corporate sustainability in the banking sector. Further, due to the intermediation role of banks in the economy, their evolution towards sustainable banking constitutes a lever for sustainability across other industries and overall sustainable development
Artículos en revistas